Types of Lianas and Supporting Plants in the Forest Area of Mount Burni Telong, Bener Meriah Ragency - Edi Hardiansyah; Cut Nurmaliah; Dewi Andayani; Djufri Djufri; Hasanuddin Hasanuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Liana is a climbing plant that characterizes tropical forests with abundant species diversity. This group of plants usually uses various types of trees to be used as supports to support their growth. The purpose of this study was to take an inventory of Liana plant species and their associations in the forest area of Mount Burni Telong, Bener Meriah Regency at an altitude of 1800 – 2100 masl. The study used a qualitative method, with the sampling technique using the line transect method which included three stations determined based on their height. In this study, 18 species of Liana plants were found spread over 3 research stations consisting of 15 families, 15 orders, and 16 genera in the Mount Burni Telong Forest, Bener Meriah Regency, and there were three tree species that were most commonly associated with Liana plants, namely Magnolia montana Blume, Artocarpus gomezianus Wall, and Pterospermum javanicum (Jungh.).Liana merupakan tumbuhan memanjat penciri hutan tropis dengan keanekaragaman jenis yang melimpah. Kelompok tumbuhan ini biasanya memanfaatkan berbagai jenis pohon untuk dijadikan penopang sebagai pendukung pertumbuhannya. Tujuan dari penelitian ini untuk menginventarisasi jenis tumbuhan Liana beserta asosiasinya di kawasan hutan Gunung Burni Telong, Kabupaten Bener Meriah pada ketinggian 1800 – 2100 mdpl. Penelitian menggunakan metode kualitatif, dengan teknik pengambilan sampel menggunakan metode line transek yang meliputi tiga stasiun yang ditentukan berdasarkan ketinggiannya. Dalam penelitian ini ditemukan sebanyak 18 jenis tumbuhan Liana yang tersebar pada 3 stasiun penelitian yang terdiri dari 15 familia, 15 ordo, dan 16 genus di kawasan Hutan Gunung Burni Telong Kabupaten Bener Meriah, dan terdapat tiga jenis pohon yang paling banyak berasosiasi dengan tumbuhan Liana yaitu Magnolia montana Blume, Artocarpus gomezianus Wall, dan Pterospermum javanicum (Jungh.).